Human evolution : our brains and behavior - Dunbar, R. I. M. (Robin Ian MacDonald), 1947- (Oxford University Press, 2016)
"This book covers the psychological aspects of human evolution with a table of contents ranging from prehistoric times to modern days. Dunbar focuses on an aspect of evolution that has typically been overshadowed by the archaeological record: the biological, neurological, and genetic changes that occurred with each "transition" in the evolutionary narrative"--